Calculus-Based Approaches for Enhancing Performance Efficiency in Computational Information System - Ghina Zalianti; Anistasya Elsa Putri; Nabila Jaisya Haq; Regita Cahyani; Pandu Herlangga; Risayd Baihaqqi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
The rapid expansion of computation-based information systems has intensified the demand for high performance, efficiency, and reliability in data processing environments. Increasing data volumes, system complexity, and real-time service requirements pose significant challenges to system optimization. This study aims to examine how calculus-based approaches contribute to enhancing performance efficiency in computational information systems. A qualitative literature review method was employed by analyzing peer-reviewed journal articles, conference proceedings, and authoritative technical reports published between 2015 and 2024. The analysis focuses on the application of differential and integral calculus in algorithm optimization, resource allocation, and system performance modeling. The findings indicate that calculus-based techniques play a critical role in reducing computational complexity, improving processing speed, and optimizing resource utilization. Calculus enables systematic performance evaluation by modeling rates of change and cumulative system behavior, allowing developers to identify optimal operational conditions. This study concludes that calculus-based approaches provide a strong mathematical foundation for improving efficiency and scalability in modern computational information systems.